ANALISIS RANTAI PASOK CABE DI KOTA KENDARI SUPPLY CHAIN ANALYSIS OF CHILI IN KENDARY CITY - Zainal Abidin (Universitas Muhammadiyah Kendari, 2018)
Chilli is an important horticultural commodity that is often increase national inflation. The research was conducted to find out the supply chain of chilli in Kendari City. The study was conducted in August - December 2016 using a structured survey of 45 respondents consist of farmers, collectors and retailers. The research result shows that the structure of the chili distribution channel in Kendari City consists of (i). collecting traders; and (ii). retailers, with a form of perfect competition market. The pattern of price formation in the majority of traders is done by summing the expected purchase and margin costs, at the level of the majority of retailers with the pattern of following the highest local prices, with the largest margin being accepted by retailers in the amount of IDR. 9,666 per kg or approximately 73% of the overall marketing margin. However, the selling price reaches Rp. 42,433 per kg, farmers get more share of price around 69%. For the next to keep the market structure and price information can be fully accessed by all parties both in the distribution channel and farmers and end consumers can be done through conventional media but ideally utilizing major social media. Furthermore, it is necessary to apply several appropriate technologies for processing chili for the development of chili products.